O Sistema Permanente de Avaliação da Educação Básica do Ceará – SPAECE-Alfa: uma avaliação a partir de contextos políticos, trajetórias institucionais e (contra)pontos no cenário escolar - Aragão, Maria Mercês Rodrigues dos Santos (2021)
This research has as objective to make an evaluation of the Permanent System of avaliation of Basic Education of the Ceará – SPAECE-Alpha, starting of political contexts, institutional trajectories and (conter) points in the school scenario. For that, it started from the analysis of essential topics that are part of the elements that support evaluative perspective that permeated this research, the evaluation in depth, considered by Rodrigues (2008) a proposal capable of subsidize a broad undertanding of the constructions that if weave in the relatioships that revolve around of the evaluation of a public policy, allowing it a comprehensive and experimental analysis: The content of politicy, the context of its formulation and its institutional trajectory. Were utilized as methodological paths in the research: bibliographic review - guided by theorists such as: Bresser Pereira 2012), Cabral Neto e Rodriguez (2007), Rodrigues (2008), Cardoso Júnior e Siqueira (2009), Carvalho (2005), Costa (2015), Gentili (2007), Gussi (2017), Lejano (2012), Federal Constitution of 1988, law guidelines and bases of national education 9394/96 and in reports of way institutional -, observation in the field school, document analysis and application of semi-structured interviews. As answer to the question raised in the research - starting political contexts, institutional trajectories and (counter) points that arise in the school scenario, What assessment can be made of the Permanent System of the evaluation of Basic Educadition of Ceará- SPAECE- Alfa? -, the results of research showed that SPAECE- Alfa viewed from the perspective of evaluation of system, although it is considered as inevitable and necessary to improve the quality of education and introduce data about undeniable evolution of level of literacy of students in the state of Ceará, it constitutes itself as an evaluation system that is under the bias of regulation and control of education action, following, therefore the same path followed and constructed historically bypublic policy evaluations.